The frequency, risk factors and spatial distribution associated with having a diagnosis of leishmaniosis in dogs in the UK in 2019 - Simon C. Kent; Dan G. O’Neill; Kim B. Stevens; Laia Solano-Gallego; Dave C. Brodbelt (PLoS ONE, 2026)
Background Leishmaniosis in dogs is an important zoonotic disease, endemic in southern Europe but is increasingly being recorded in other parts of Europe including the UK. This study aimed to update the epidemiological knowledge of leishmaniosis in the UK dog population. Methods The estimated prevalence of leishmaniosis diagnosis in dogs under care at VetCompass UK participating practices in 2019 was calculated. Risk factor associations for leishmaniosis were investigated using mixed-effects multivariable logistic regression modelling. The spatial distribution of leishmaniosis was explored using standardised morbidity rates (SMR) at regional and county levels, and Moran’s I was used to identify significant spatial autocorrelation. Results The estimated annual prevalence was calculated as 0.0434% (95% CI 0.0427–0.0443) with 976 cases from this population of dogs (n = 2,250,741). Most of the dogs with leishmaniosis had originated from outside the UK (955/976, 97.9%) and of those, 60.8% (581) had already been diagnosed with leishmaniosis pre-import. In the risk factor analysis, the odds of leishmaniosis were higher in males (OR 1.29, 95% CI 1.12–1.49) and neutered dogs (OR 6.42, 95% CI 4.43–9.29) compared to female and entire dogs, respectively. Purebreds overall had lower odds of leishmaniosis compared to crossbreeds (OR 0.24, 95% CI 0.20–0.28) but there were specific breeds such as Brittany Spaniels (OR 53.0, 95% CI 25.3–111.1), Ibizan Hounds (OR 43.8, 95% CI 9.20–208.3) and English Pointers (OR 28.6, 95% CI 14.5–56.4) which had much higher odds of being a case compared to crossbreeds. Spatial analysis identified more leishmaniosis cases in southern England than were expected by random chance (SMR > 1). Conclusions This study identifies that imported animals are the commonest source of dogs having a leishmaniosis diagnosis. The breeds with very high odds for leishmaniosis may reflect selection bias towards breeds more likely to be imported, rescued or travelled from endemic areas rather than high intrinsic risk in these breeds towards leishmaniosis. These results support and update previous studies indicating that most cases are diagnosed in southern England.